Low efficacy of mebendazole against hookworm in Vietnam: two randomized controlled trials. - Flohr, C; Tuyen, L; Lewis, S; Minh, T; Campbell, J; Britton, J; Williams, H; Hien, T; Farrar, J; Quinnell, R (2007)
Vietnam is participating in a global de-worming effort that aims to treat 650 million school children regularly by 2010. The treatment used in Vietnam is single dose oral mebendazole (Phardazone) 500 mg. We tested the efficacy of single dose mebendazole 500 mg in the therapy of hookworm infection in a randomized double-blind placebo-controlled trial among 271 Vietnamese schoolchildren. The treatment efficacy of single dose mebendazole in children did not differ significantly from placebo, with a reduction in mean eggs per gram of feces relative to placebo of 31% (95% CI -9 to 56%, P = 0.1). In light of these findings we then carried out a similar randomized trial comparing triple dose mebendazole, single dose albendazole, and triple dose albendazole against placebo in 209 adults in the same area. The estimated reduction in mean post-treatment eggs per gram of feces relative to placebo was 63% (95% CI 30-81%) for triple mebendazole, 75% (47-88%) for single albendazole, and 88% (58-97%) for triple albendazole. Our results suggest that single dose oral mebendazole has low efficacy against hookworm infection in Vietnam, and that it should be replaced by albendazole. These findings are of major public health relevance given the opportunity costs of treating entire populations with ineffective therapies. We recommend that efficacy of anti-helminth therapies is pilot tested before implementation of national gut worm control programs.